Design and Analysis of 1MHz Class-E Power Amplifier for Load and Duty Cycle Variations - Yusmarnita Yusop; Mohd Shakir Md Saat; Siti Huzaimah Husin; Sing Kiong Nguang; Imran Hindustan (Institute of Advanced Engineering and Science, 2016)
This paper presents the simulation and experimental of Class-E power amplifier which consists of a load network and a single transistor. The transistor is operated as a switch at the carrier frequency of the output signal. In general, Class-E power amplifier is often used in designing a high frequency ac power source because of its ability to satisfy the zero voltage switching (ZVS) conditions efficiently even when working at high frequencies with significant reduction in switching losses. In this paper, a 10W Class-E power amplifier is designed, constructed, and tested in the laboratory. SK40C microcontroller board with PIC16F877A is used to generate a pulse width modulation (PWM) switching signal to drive the IRF510 MOSFET. To be specific, in this paper, the effect on switching and performance at 1MHz frequency are studied in order to understand the Class-E inverter behavior. Performance parameters relationships were observed and analysed in respect to the load and duty cycle. Theoretical calculations, simulation and experimental results for optimum operation using selected component values are then compared and presented.